2021
DOI: 10.1002/anie.202015177
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Mechanistic Study of the Radical SAM Enzyme ArsS Involved in Arsenosugar Biosynthesis

Abstract: Arsenosugars are a group of arsenic‐containing ribosides that are found predominantly in marine algae but also in terrestrial organisms. It has been proposed that arsenosugar biosynthesis involves a key intermediate 5′‐deoxy‐5′‐dimethylarsinoyl‐adenosine (DDMAA), but how DDMAA is produced remains elusive. Now, we report characterization of ArsS as a DDMAA synthase, which catalyzes a radical S‐adenosylmethionine (SAM)‐mediated alkylation (adenosylation) of dimethylarsenite (DMAsIII) to produce DDMAA. This radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Because multiple reaction turnovers were observed in the absence of external reductant, it is likely that upon decarboxylation the electron could go back to the [4Fe-4S] cluster to regenerate its active +1 state . A similar redox-neutral reaction has also been observed for other radical SAM enzymes. …”
Section: The Anaerobic Cpo Hemnmentioning
confidence: 64%
“…Because multiple reaction turnovers were observed in the absence of external reductant, it is likely that upon decarboxylation the electron could go back to the [4Fe-4S] cluster to regenerate its active +1 state . A similar redox-neutral reaction has also been observed for other radical SAM enzymes. …”
Section: The Anaerobic Cpo Hemnmentioning
confidence: 64%
“…Aminofutalosine synthase (MqnE) is a radical SAM enzyme involved in the futalosine-dependent menaquinone biosynthesis and is the first of only four examples of radical SAM enzymes in which the 5′-deoxyadenosyl radical is utilized for C–X bond formation (X = C, S, As) rather than for H atom abstraction. Mechanistic studies on MqnE have established the intermediacy of the captodative radical 3 as well as an aryl radical anion 7 (Figure A), , and the structure of MqnE complexed to 8 has recently been determined . The rearrangement reaction ( 3 – 5 ) can be blocked by replacing the bridging oxygen in the native substrate with a methylene group.…”
mentioning
confidence: 99%
“…2 In fact, it was recently reported that the conversion of DMAs(III) to 5′-deoxy-5′dimethylarsinoyl-adenosine, a key intermediate of the arsenosugars, is catalyzed by the radical SAM enzyme ArsS, which is distributed in a wide range of bacterial phyla. 4,5 Arsenosugars and AsFAs are thought to be converted to As-containing complex lipids, which comprise the majority of organoarsenic natural products, or degraded to arsenobetaine (Figure S1). 2 On the other hand, the soil bacterium Burkholderia gladioli GSRB05 was reported to convert As(III) to the As-bearing amino acid arsinothricin in a different manner; a C−As bond is formed between inorganic As(III) and a 3-amino-3-carboxypropyl radical by the radical SAM enzyme ArsL, and subsequent As-methylation by the SAM methyltransferase ArsM and autoxidation complete arsinothricin biosynthesis (Figure S1).…”
Section: ■ Introductionmentioning
confidence: 99%